Superconductivity in an Orbital‐Reoriented SnAs Square Lattice: A Case Study of Li0.6Sn2As2 and NaSnAs. Issue 10 (24th January 2023) - Wang, Junjie; Ying, Tianping; Deng, Jun; Pei, Cuiying; Yu, Tongxu; Chen, Xu; Wan, Yimin; Yang, Mingzhang; Dai, Weiyi; Yang, Dongliang; Li, Yanchun; Li, Shiyan; et al.
Abstract: Searching for functional square lattices in layered superconductor systems offers an explicit clue to modify the electron behavior and find exotic properties. The trigonal SnAs3 structural units in SnAs‐based systems are relatively conformable to distortion, which provides the possibility to achieve structurally topological transformation and higher superconducting transition temperatures. In the present work, the functional As square lattice was realized and activated in Li0.6 Sn2 As2 and NaSnAs through a topotactic structural transformation of trigonal SnAs3 to square SnAs4 under pressure, resulting in a record‐high T c among all synthesized SnAs‐based compounds. Meanwhile, the conductive channel transfers from the out‐of‐plane p z orbital to the in‐plane p x + p y orbitals, facilitating electron hopping within the square 2D lattice and boosting the superconductivity. The reorientation of p ‐orbital following a directed local structure transformation provides an effective strategy to modify layered superconducting systems. Abstract : A new type of structure unit SnAs4 is realized via a topotactic phase transformation under high pressure, which leads to a record‐high superconducting transition temperature ( T c ) of 7.5 K among all the synthesized SnAs‐based compounds. It is the synergistic effect of orbital reorientation and charge redistribution from the p z to the p x + p y orbitals that facilitates the electron hopping within the square 2D lattice and boosts the superconductivity.